Предмет: Алгебра,
автор: ludmila6088
Ответы
Автор ответа:
0
Ответ:
х1=-1 ; х2=1/3 ; х3=0,5
Объяснение:
(x+1)*(6x^2-5x+1)=0
x+1=0
6x^2-5x+1=0
x1=-1
6x^2-5x+1=0
x2=0.5 ; x3=1/3
Автор ответа:
0
Ответ:
x = {-1; 1/3; 1/2}
Пошаговое объяснение:
x+1 = 0
x = -1
6х^2 -5х+1 = 0
D = (-5)^2 - 4 * 6 *1 = 1
√D = ±1
x = (5±1 ) /(2*6);
x1 = 1/2;
x2 =1/3
Похожие вопросы
Предмет: Українська література,
автор: nat48355799
Предмет: Математика,
автор: daniilrudenko81165
Предмет: Немецкий язык,
автор: nedostoev2003
Предмет: История,
автор: звідки
Предмет: Литература,
автор: medjidov1zaur